Pengawasan Partisipatif, SDM, dan Efektivitas Kinerja Bawaslu Maluku Tenggara - Alwi La Hamid; Zainal Abidin Rengifurwarin; Josep Antonius Ufi (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This article analyzes the influence of participatory supervision and human resource management on the effectiveness of election supervision performance at the Election Supervisory Body (Bawaslu) of Southeast Maluku Regency. The study uses a quantitative associative design involving 68 respondents consisting of Bawaslu members, secretariat staff, and supporting/ad hoc supervision personnel. Data were collected through a closed Likert-scale questionnaire and analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression. The findings show that participatory supervision has a positive and significant effect on supervision effectiveness (B = 0.776; t = 10.214; p < 0.001) and becomes the most dominant predictor. Conversely, human resource management has a positive but non-significant partial effect (B = 0.092; t = 1.114; p = 0.269). Simultaneously, both variables significantly explain supervision effectiveness (F = 323.627; p < 0.001; Adjusted R2 = 0.906). The study implies that participatory public oversight should be strengthened alongside contextual HR development, especially in archipelagic electoral supervision settings.